[1-(5-Bromo-2-oxidobenzylidene)thiosemicarbazidato-[kappa]3O,N1,S](pyridine-[kappa]N)nickel(II) - Pederzolli, Fernanda Rosi Soares (2012)
The reaction of 5-bromosalicylaldehyde thiosemicarbazone with nickel acetate tetrahydrate and pyridine yielded the title compound, [Ni(C8H6BrN3OS)(C5H5N)]. The NiII atom is four-coordinated in a square-planar environment by one deprotonated dianionic thiosemicarbazone ligand, acting in a tridentate chelating mode through N, O and S atoms forming two metalla-rings, and by one pyridine molecule. The complex molecules are linked into dimers by pairs of centrosymmetrical N-H...N interactions. In addition, molecules are connected through intermolecular Br...Br interactions [3.545 (1) Å], forming chains along the b-axis direction.